Generalized Pre α-Regular and Generalized Pre α-Normal Spaces in Topological Spaces - Patil, P. G.; Pattanashetti, Bhadramma (Iraqi Journal of Science, 2023)
The concept of separation axioms constitutes a key role in general topology and all generalized forms of topologies. The present authors continued the study of gpα-closed sets by utilizing this concept, new separation axioms, namely gpα-regular and gpα-normal spaces are studied and established their characterizations. Also, new spaces namely gpα-Tk for k = 0, 1, 2 are studied.